Caracterização da ação vasodilatadora do extrato aquoso obtido das folhas de Alpinia zerumbet K.Schum em aorta de ratos - Rocha, Hidemburgo Gonçalves (2012)
The Alpinia zerumbet is a plant commonly found in the northeastern region of Brazil. This plant is popularly known as colony and is widely used in folk medicine for its diuretic and antihypertensive properties. The aim of this study was to investigate whether the aqueous extract of leaves of A. zerumbet (EAAz) had vasodilator activity in rat aorta pre-contracted with phenylephrine and to elucidate its mechanism of action. Male Wistar rats (250-300 g) from the vivarium of UFC, were killed by cervical dislocation and the thoracic aorta removed and dissected. The aortic rings (4-5 mm) were mounted in organ cameras, and containing Krebs solution aerated with carbogen at 37 ° C to measure changes in isometric tension. The endothelium of the aortic rings was removed mechanically to study their involvement in the vasodilator effect of EAAz. To study the involvement of nitric oxide (NO), cGMP, prostanoid, potassium channels activated by Ca2+, reactive oxygen species and activation of enzymes kinases Src and PI3 kinase, the preparations were treated respectively with L-NAME (100 µM ), ODQ (10 µM), indomethacin (10 µM), carybdotoxin (100 nM) plus apamin (100 nM), MnTMPyP (100 µM), catalase (500 U / ml), PEG-catalase (500 U/ ml), SOD (500 U / ml) and PP2 (20 µM), wortmannin (300 nM). The vasodilatory effect of EAAz (0.05, 0.15, 0.5, 1.5, 15 and 50 µg / mL), acetylcholine (10-8 - 10-5 M) and sodium nitroprusside (10-8 M ) were evaluated in the aorta of rats pre-contracted with phenylephrine (10-8 - 3x10-8 M) before and after treatment with the specific inhibitors. EAAz induced vasodilation was dependent and endothelium mediated by NO via cGMP as the vascular relaxation was abolished in the presence of the methyl ester of NG-nitro-L-arginine and ODQ. Vasodilation was also reduced by MnTMPyP (mimetic cellular permeant SOD), catalase polyethylene glycol, PP2 (Src kinase inhibitor) and wortmannin (inhibitor of phosphoinositide 3-kinase). The route of production of ROS induced EAAz was significantly prevented by the action of MnTMPyP and PEG-catalase. There was also the inhibition of the kinase ROS/PI3 / Src kinase that are involved in the activation of the eNOS. The EAAz caused an endothelium-dependent relaxation via NO / cGMP with the possible involvement of ROS and Src kinase and phosphoinositide 3-kinase-dependent Akt. Taking us to the conclusion that the vascular relaxation induced by EAAz could explain the traditional use of the tea leaves of A. zerumbet for the treatment of hypertension.